Odpowiedź:
a)
3x + 6 = 9
3x = 9 - 6
3x = 3
x = 1
b)
5 = 3 + 7x
5 - 3 = 7x
7x = 2
x = [tex]\frac{2}{7}[/tex]
c)
0,5x = 11
x = 22
d)
[tex]\frac{4}{9} x=\frac{1}{3} \\\\x=0,75[/tex]
e)
[tex]\frac{1}{3} x+1=5\\\\x+3=15\\\\x=15-3\\\\x=12[/tex]
f)
-x - 3 - x - 4 = 1
-x - x = 1 + 4 + 3
-2x = 8
x = -4
g)
-5x = 16
x = [tex]-\frac{16}{5}=-3\frac{1}{5}[/tex]
h)
[tex]\frac{x}{4}=9\\\\x=36[/tex]
i)
x - 14 = -17
x = -17 + 14
x = -3
j)
-3x + 4 = 10
-3x = 10 - 4
-3x = 6
x = -2
k)
2x - 7 = -11
2x = -11 + 7
2x = -4
x = -2
l)
x - 4 + 3x = -20
x + 3x = -20 + 4
4x = -16
x = -4
m)
5 - 2x + 7 = 14
-2x = 14 - 5 - 7
-2x = 2
x = -1
n)
-2x = 16
x = -8
o)
2x - 5 - x - 3 = 8
2x - x = 8 + 5 + 3
x = 16